Comprehensive Simple Model on Solid Oxide Fuel Cells. (15th July 2012) - Arteaga-Pérez, Luis E.; Peralta-Suárez, Luis M.; Casas-Ledón, Yannay; Prieto-García, Julio O.
Abstract : The mathematical, multiphysic, multidimensional, and electrochemical modelation of a high temperature solid oxide fuel cell system (planar electrolyte-supported configuration) is discussed in the present paper. The mass transport within the cell is studied using the Stefan-Maxwel model, and the momentum balance is solved by means of Navier-Stokes and Brinkman equations, respectively. On the other hand, the energy balance includes the generation term coupled with the convection and conduction equations. It was demonstrated that the diffusion resistances play an important role in the cell performance, and the oxidant concentration is enough high to work at fuel utilization coefficient of 0.8. The current density suffers a reduction (10 A/m 2 to 1.5 ∗ 10 − 3 A/m 2 ) due to the variation of reactants concentration at the cell outlet and the diffusive flux resistances. The developed models can be used to further analyses and to study a solid oxide fuel cell working with other fuels but hydrogen.